Inhibition of the glutaredoxin and thioredoxin systems and ribonucleotide reductase by mutant p53-targeting compound APR-246 - Lena Haffo (Scientific Reports, 2018)
Abstract The tumor suppressor p53 is commonly inactivated in human tumors, allowing evasion of p53-dependent apoptosis and tumor progression. The small molecule APR-246 (PRIMA-1Met) can reactive mutant p53 in tumor cells and trigger cell death by apoptosis. The thioredoxin (Trx) and glutaredoxin (Grx) systems are important as antioxidants for maintaining cellular redox balance and providing electrons for thiol-dependent reactions like those catalyzed by ribonucleotide reductase and peroxiredoxins (Prxs). We show here that the Michael acceptor methylene quinuclidinone (MQ), the active form of APR-246, is a potent direct inhibitor of Trx1 and Grx1 by reacting with sulfhydryl groups in the enzymes. The inhibition of Trx1 and Grx1 by APR-246/MQ is reversible and the inhibitory efficiency is dependent on the presence of glutathione. APR-246/MQ also inhibits Trxs in mutant p53-expressing Saos-2 His-273 cells, showing modification of Trx1 and mitochondrial Trx2. Inhibition of the Trx and Grx systems leads to insufficient reducing power to deoxyribonucleotide production for DNA replication and repair and peroxiredoxin for removal of ROS. We also demonstrate that APR-246 and MQ inhibit ribonucleotide reductase (RNR) in vitro and in living cells. Our results suggest that APR-246 induces tumor cell death through both reactivations of mutant p53 and inhibition of cellular thiol-dependent redox systems, providing a novel strategy for cancer therapy.